Traditional Madurese Engagement Amids the Social Change of the Kangean Society - Fahmi Reza Alfani; Hairus Salikin; Muta’allim; Hosaini; Hasan Sayfullah (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2021)
Kangean is an island that has various traditions, one of which is the engagement tradition. Today, the engagement tradition has undergone a drastic shift, due to the presence of technological media, such as television, cell phones, the internet, and the like. Television, which is basically a medium of entertainment for the wider community, however, for the kangean community, television is one of the causes of social and cultural changes. This study aims to uncover and describe the causes of these changes. This study uses data analysis. Qualitative methods are methods that aim to obtain descriptive data. The data in this study are conversations related to the causes of socio-cultural shifts, the data is transcribed into written texts. The data was collected by interviewing, selecting, describing and verification techniques. Data were analyzed by using descriptive qualitative method which is based on Siswantoro's theory. The results of this study indicate that non-educational shows on television such as soap opera films, promiscuty, blue film, tiktok, life style, speaking style and dress patterns are greatly affect the kangean community especially among teenagers. The negative affects for Kangean teenagers are on social life, lifestyle, speaking style, promiscuty, drug addicts, violating customs, traditions and culture. Therefore, policies are needed to limit the scope of globalization to which ones should be implemented and which should be rejected. This requires the role of the government of the kangean community to act through policies that are more directed at socio-cultural considerations.